“We Stretched the Rules”: How Street-Level Bureaucrats in Schools Shape Newcomers’ Access to Resources - Heike Hanhörster; Cornelia Tippel (Urban Planning, 2024)
Schools play a crucial role for migrant families’ arrival processes. Educational guidelines, procedures, and requirements (such as admission waiting lists or school curricula) are translated into practices on the ground, with many school professionals acting as policy intermediaries shaping (in)formal policy-making and facilitating newcomers’ access to resources. Analysing the everyday work and practices of school bureaucrats can help better understand their formal and informal roles in migration governance and newcomers’ access to resources. Drawing on Lipsky’s (1980/2010) concept of street-level bureaucracy, this article looks at primary schools in Nordstadt, Dortmund (Germany). The schools are situated in a context with a long history of arrival and a high influx of newcomers in recent years. Participant observation and interviews with school staff (headteachers, teachers, and social workers) illustrate that the agency of street-level bureaucrats (SLBs) can involve more than just coping with inadequate resources: SLBs can go the extra mile, for example, “bending” curricula to suit circumstances. The article focuses on how school staff do not necessarily limit themselves to their standard tasks but expand their range of activities formally and sometimes quite informally, even though they are confronted with diverse demands and many work at the limits of their capacities. By analysing schools as arrival infrastructure through the lens of SLBs, this article contributes to a better understanding of how migrant newcomers’ needs and state requirements are mediated. While the embeddedness of SLBs in such macro-factors as the type of welfare regime or political culture and organisational settings is well described, their embeddedness at the city and especially the neighbourhood levels has been studied much less systematically. One enabling factor for SLBs’ commitment to contribute under (un)certain conditions to facilitating newcomers’ access to resources is their multiple embeddedness and particularly their local collaboration in an ecosystem of interconnected social infrastructures.